Method for regeneration and modification utilization of graphite in wet leaching carbon residue of retired lithium battery

Through multi-field coupling strengthening reaction technology and solution modification technology, the high impurity content, complex processes and secondary pollution problems of graphite resource recovery in wet leaching carbon slag in retired lithium batteries are solved, and the clean recycling and modification utilization of high-purity graphite resources are achieved, with the advantages of simplifying processes, reducing costs and improving economic benefits.

CN119753762APending Publication Date: 2025-04-04GUIZHOU NORMAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411971922.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, when recycling graphite resources in the wet leaching of carbon slag in retired lithium batteries, there are problems of high impurity content, complex process flow and secondary pollution risks.

Method used

Multi-field coupling strengthening reaction technology and solution modification technology are adopted to achieve clean and efficient recycling of graphite resources through multi-stage refinement, water washing and modification treatment, and high dosage utilization is achieved in the field of carbon materials for aluminum.

Benefits of technology

High purity recovery of graphite resources (carbon content ≥99.90 wt%) is achieved, the process flow is simplified, secondary pollution is avoided, treatment costs are reduced, and economic benefits are significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of solid waste treatment, and particularly relates to a method for regeneration and modified utilization of graphite in decommissioned lithium battery wet leaching carbon residues, which successfully realizes clean recovery and modified utilization of commercial graphite resources in the decommissioned lithium battery wet leaching carbon residues through combination of a multi-external-field synergistic strengthening means and a solution modification technology. The whole treatment link is simple in process route and free of secondary pollution, the digesting agent and the aqueous solution can be recycled, and the economic and environment-friendly value is remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste treatment, and in particular to a method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries. Background Art

[0002] Lithium-ion batteries are widely used in new energy vehicles, 3C digital products, energy storage systems, aerospace and other fields. Due to overcharging, electrolyte decomposition, self-discharge, and electrode material structure damage during long-term service, lithium-ion batteries will experience capacity decay, resulting in the scrapping and retirement of lithium-ion batteries. At present, high-value metals such as nickel, cobalt, manganese, and lithium can be successfully recovered through hydrometallurgical processes, but the resulting leached carbon slag has not received widespread attention. It is mostly in a stockpile state or used as a low-value fuel, wasting a large amount of commercial graphite resources and posing a serious threat to the surrounding environment. Therefore, achieving clean recovery and efficient utilization of graphite resources in leached carbon slag is conducive to promoting the green and sustainable development of the new energy industry.

[0003] At present, a lot of research has been carried out on the recycling and utilization of carbon slag from wet leaching of retired lithium batteries.

[0004] Chinese invention patent CN115304059B discloses a method for recycling carbon slag from retired batteries, which uses sulfuric acid and fluoride salts to roast the carbon slag from retired batteries, and dissolves non-carbon soluble impurities through multiple water washings to achieve the recovery of graphite resources, and the roasting flue gas is passed into an absorption liquid for absorption. Chinese invention patent CN112086703B proposes a method for recycling carbon slag from retired batteries, which mechanically mixes the carbon slag with fluoride salts, and achieves phase transformation and dissolution removal of non-carbon impurities through fluoridation roasting combined with wet leaching, thereby efficiently recovering graphite resources from the carbon slag from retired batteries. The above method recovers graphite with high purity and low impurity content, and involves the emission and transfer of highly corrosive hydrogen fluoride gas during the treatment process, with a significant risk of secondary pollution. At the same time, no resource utilization path for regenerated graphite is proposed.

[0005] Chinese invention patent CN116969453A discloses a method for recovering graphite from waste carbon residue of retired lithium-ion batteries, which uses a flotation process to pre-treat the waste residue of retired lithium-ion batteries, and then deeply purifies the flotation concentrate by pressurized alkaline leaching to recover high-purity graphite resources. This method recovers graphite with a carbon content of ≥99.9wt%, but the process is extremely complicated, involving multiple links such as flotation, pressurized leaching, and water washing and purification, and flotation waste liquid, alkaline leaching waste liquid and water leaching waste liquid will be generated during the recovery process, posing a serious threat to the ecological environment.

[0006] Chinese invention patent CN116639686A proposes a method for preparing porous graphite using waste lithium-ion battery carbon residue, which involves refining and sorting the waste carbon residue of retired lithium batteries, then co-baking the waste carbon residue with calcium fluoride and concentrated sulfuric acid, and washing the porous graphite product. The flue gas is absorbed by a calcium salt solution. This method can obtain porous graphite with a purity of ≥99wt%, but since graphite has a regular lamellar structure, it is difficult to make holes, resulting in a specific surface area of ​​only 440m 2 / g, the value of resource utilization is relatively low. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a method for regenerating and modifying graphite in carbon slag extracted from retired lithium batteries by wet leaching, and to realize clean and efficient regeneration of high-purity graphite in carbon slag extracted by wet leaching by utilizing the technical idea of ​​multi-external field coupling enhancement reaction. At the same time, the regenerated graphite is purified and modified in multiple water washing links to realize high-dosage utilization of modified regenerated graphite in the field of carbon materials for aluminum. The method has the characteristics of simple process, low processing cost, no secondary pollution and obvious economic benefits.

[0008] According to one aspect of the present invention, the present invention provides the following technical solution:

[0009] A method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries, comprising the following steps:

[0010] S1. Perform multi-level refinement on the carbon slag extracted by wet leaching of retired lithium batteries to obtain pre-treated materials;

[0011] S2, adding the pretreated material and the digester into the polytetrafluoroethylene liner, then adding the polytetrafluoroethylene grinding balls and sealing, and then placing the polytetrafluoroethylene liner into the multi-external field coupling enhanced reaction device for reaction;

[0012] S3, after the reaction is completed, the remaining solid material is subjected to a first-stage water washing treatment, and after filtering, a leached residue 1 and a leached liquid 1 are obtained; then the leached residue 1 is subjected to a second-stage water washing treatment, and after filtering, a leached residue 2 and a leached liquid 2 are obtained; then, the leached residue 2 is subjected to a third-stage water washing treatment with an aqueous solution added with a modifier, and after filtering, a modified material and a leached liquid 3 are obtained;

[0013] S4, subjecting leachate 1 to alkaline impurity removal treatment, and then adjusting the pH value with a buffer, recovering the digestion agent by freeze concentration, and recycling it for multi-external field coupling enhanced reaction; leachate 2 is countercurrently circulated for a first-stage water washing treatment, and leachate 3 is supplemented with a modifier and reused for a third-stage water washing treatment;

[0014] S5, mixing the modified material with the carbon aggregate to obtain a mixed material, and then adding the modifier to the binder to obtain a strong wetting binder;

[0015] S6. The mixed material and the strong wetting binder are subjected to heating, kneading, vibration molding, high-temperature roasting and shaping treatment to obtain a carbon material product for aluminum.

[0016] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from retired lithium batteries by wet leaching described in the present invention, in which: in the step S1, the particle size range of the pretreated material is any one of <1 mm, <0.5 mm, <0.15 mm, and <0.074 mm.

[0017] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from a retired lithium battery by wet leaching described in the present invention, in which: in the step S1, the lithium battery is one or more of a ternary lithium battery, a lithium cobalt oxide battery, a lithium iron phosphate battery, and a lithium manganese oxide battery.

[0018] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from a retired lithium battery by wet leaching described in the present invention, wherein: in the step S2, the digester is one or more of ammonium bifluoride, ammonium fluoride, sodium bifluoride, and sodium hydroxide; the mass ratio of the pretreated material to the digester is 1:(0.1-1).

[0019] As a preferred embodiment of the method for regenerating and modifying graphite from carbon slag by wet leaching of retired lithium batteries described in the present invention, in step S2, polytetrafluoroethylene grinding balls are added according to a ball-to-material mass ratio of (1-20):1.

[0020] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from retired lithium batteries by wet leaching, the step S2 comprises the following steps: the reaction temperature is 100 to 200°C, the reaction time is 10 to 60 minutes, and the vibration frequency is 200 to 2000 r / min.

[0021] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from a retired lithium battery by wet leaching described in the present invention, wherein: in the step S3, the liquid-solid ratio during the first water washing treatment is (5-40):1; the liquid-solid ratio during the second water washing treatment is (5-30):1; the liquid-solid ratio during the third water washing treatment is (5-20):1; the water washing temperature is 20-90°C, and the water washing time is 10-100 min.

[0022] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from retired lithium batteries by wet leaching described in the present invention, wherein: in step S3, the modifier is one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; the amount of the modifier added is 0.1 to 10% of the volume of the aqueous solution.

[0023] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from retired lithium batteries by wet leaching described in the present invention, wherein: in step S4, the buffer solution is one or more of hydrofluoric acid, ammonium bifluoride, ammonium fluoride, and carbonic acid; the pH value is adjusted to 1-4 using the buffer solution.

[0024] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries according to the present invention, wherein: in step S5, the mass ratio of the modified material to the carbon aggregate is 1:99-50:50; the mixing time is 30-180 minutes. The carbon aggregate is one or more of electrically calcined anthracite, artificial graphite, asphalt coke, calcined petroleum coke, and residual electrodes.

[0025] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from retired lithium batteries by wet leaching described in the present invention, wherein: in step S5, the binder is one or more of modified asphalt, bio-asphalt, coal tar, epoxy resin, and phenolic resin; the amount of the modifier added is 0.01 to 1 wt% of the binder.

[0026] As a preferred embodiment of the method for regenerating and modifying graphite in carbon slag from retired lithium batteries by wet leaching described in the present invention, wherein: in the step S6, the mass ratio of the mixed material to the strong wetting binder is 80:20-90:10; the carbon material product for aluminum is a prebaked anode or cathode carbon block.

[0027] The beneficial effects of the present invention are as follows:

[0028] The present invention proposes a method for regenerating and modifying graphite in carbon slag extracted from retired lithium batteries by wet leaching. By combining multiple external field synergistic enhancement means with solution modification technology, the clean recovery and modified utilization of commercial graphite resources in carbon slag extracted from retired lithium batteries by wet leaching are successfully achieved. The process route of the entire disposal link is simple and does not generate secondary pollution. The digester and aqueous solution can be recycled, and the economic and environmental value is significant. DETAILED DESCRIPTION

[0029] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention proposes a method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries, which utilizes multiple external field synergistic enhancement means to efficiently recover commercial graphite resources in carbon slag extracted by wet leaching of retired lithium batteries, and realizes cross-industry resource utilization of regenerated graphite in the field of aluminum carbon materials through modification, and has the following technical advantages:

[0031] (1) Through mechanical activation and high temperature and high pressure environment multi-external field coupling enhancement, low-cost and efficient recovery of graphite resources with a carbon content of ≥99.90wt% was successfully achieved under low reaction conditions (digester ratio ≤1:1, reaction temperature ≤200℃, reaction time ≤60min).

[0032] (2) The use of a closed reaction device avoids the emission and transfer of highly corrosive gases during the reaction process, eliminating the risk of environmental pollution caused by hazardous gases. At the same time, the released flue gas reattaches to the surface of the material during the condensation process and further reacts deeply with the residual non-carbon impurities.

[0033] (3) The modification treatment is directly introduced into the multi-stage water washing process, which shortens the treatment process and significantly improves the binder wettability of the recycled graphite. The contact angle of the modified graphite is ≤20°, overcoming the technical bottleneck of poor wettability between graphite materials and binders.

[0034] (4) The digester was regenerated by combining alkaline impurity removal, pH control and freeze concentration. The digester recovery rate was ≥85.0%, which significantly reduced the reagent cost of the multi-field coupling enhanced reaction link and avoided the environmental pollution risk of fluoride-containing wastewater.

[0035] (5) Use modifiers to regulate the wettability of binders, and combine with modified graphite to improve the overall wetting effect of carbon aggregate and binder from the source of raw materials, so as to ensure the performance of carbon materials for aluminum prepared by modified graphite blending. For prebaked anodes: apparent density ≥1.55g / cm 3 , compressive strength ≥ 32MPa, room temperature resistivity ≤ 57μΩ·m, ash content ≤ 0.8wt%, CO2 reactivity ≥ 83%. For cathode carbon blocks: apparent density ≥ 1.57g / cm 3 , compressive strength ≥ 24MPa, room temperature resistivity ≤ 30μΩ·m, ash content ≤ 4wt%, sodium expansion rate ≤ 0.7%.

[0036] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0037] Embodiment 1

[0038] A method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries, comprising the following steps:

[0039] S1. Multi-level refinement of the carbon slag from the wet leaching of retired ternary lithium batteries to obtain pre-treated materials with a particle size range of <0.074mm.

[0040] S2. The pretreated material and ammonium bifluoride are added to the polytetrafluoroethylene liner at a mass ratio of 1:0.5, and then polytetrafluoroethylene grinding balls are added at a ball-to-material mass ratio of 8:1 and sealed. The polytetrafluoroethylene liner is further loaded into a multi-external field coupling enhanced reaction device. The reaction temperature is 200°C, the reaction time is 60min, and the vibration frequency is 1200r / min.

[0041] S3, after the reaction is completed, the remaining solid material is subjected to a first-stage water washing treatment according to a liquid-solid ratio of 25:1, and after filtering, leaching residue 1 and leachate 1 are obtained; then, the leaching residue 1 is subjected to a second-stage water washing treatment according to a liquid-solid ratio of 20:1, and after filtering, leaching residue 2 and leachate 2 are obtained; further, a silane coupling agent is added to the aqueous solution according to a volume ratio of 0.1%, and then the leaching residue 2 is subjected to a third-stage water washing treatment according to a liquid-solid ratio of 15:1, and after filtering, a modified material and leachate 3 are obtained. The carbon content of the modified regenerated graphite is 99.98wt%, and the contact angle is 18.15°.

[0042] S4, the leachate 1 is subjected to alkaline impurity removal treatment, and then the pH value is adjusted to 3 with hydrofluoric acid, and the digestion agent is recovered by freeze concentration and circulated for multi-field coupling enhanced reaction. The leachate 2 is circulated in countercurrent for the first stage water washing treatment, and the leachate 3 is supplemented with a modifier and reused for the third stage water washing treatment. The recovery rate of ammonium bifluoride is 88.64%.

[0043] S5, adding the modified material, calcined petroleum coke and residual anode mixture in a mass ratio of 5:95 into a three-dimensional mixer for uniform mixing to obtain a mixed material, and the mixing time is 60 minutes. Then, adding the silane coupling agent in a mass ratio of 0.5wt% into the modified asphalt and bio-asphalt mixed binder to obtain a strong wetting binder.

[0044] S6. The mixed material and the strong wetting binder are heated and kneaded in a mass ratio of 85:15, vibrated and formed, high-temperature calcined and shaped to obtain a prebaked anode for aluminum. The apparent density of the prebaked anode is 1.58 g / cm 3 , compressive strength is 37MPa, room temperature resistivity is 52μΩ·m, ash content is 0.3wt%, and CO2 reactivity is 88%.

[0045] Embodiment 2

[0046] A method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries, comprising the following steps:

[0047] S1. Multi-level refinement of the carbon slag extracted from the wet leaching of retired ternary lithium batteries to obtain pre-treated materials with a particle size range of <0.15mm.

[0048] S2. The pretreated material and ammonium bifluoride are added to the polytetrafluoroethylene liner at a mass ratio of 1:0.3, and then polytetrafluoroethylene grinding balls are added at a ball-to-material mass ratio of 6:1 and sealed. The polytetrafluoroethylene liner is further loaded into a multi-external field coupling enhanced reaction device. The reaction temperature is 150°C, the reaction time is 30 minutes, and the vibration frequency is 800 r / min.

[0049] S3, after the reaction is completed, the remaining solid material is subjected to a first-stage water washing treatment according to a liquid-solid ratio of 20:1, and after filtering, leaching residue 1 and leachate 1 are obtained; then, the leaching residue 1 is subjected to a second-stage water washing treatment according to a liquid-solid ratio of 15:1, and after filtering, leaching residue 2 and leachate 2 are obtained; further, a silane coupling agent is added to the aqueous solution according to a volume ratio of 0.1%, and then the leaching residue 2 is subjected to a third-stage water washing treatment according to a liquid-solid ratio of 10:1, and after filtering, a modified material and leachate 3 are obtained. The carbon content of the modified regenerated graphite is 99.92wt%, and the contact angle is 19.23°.

[0050] S4, the leachate 1 is subjected to alkaline impurity removal treatment, and then the pH value is adjusted to 3.5 with hydrofluoric acid, and the digestion agent is recovered by freeze concentration and circulated for multi-field coupling enhanced reaction. The leachate 2 is circulated in countercurrent for the first stage water washing treatment, and the leachate 3 is supplemented with a modifier and reused for the third stage water washing treatment. The recovery rate of ammonium bifluoride is 86.17%.

[0051] S5, adding the modified material, calcined petroleum coke and residual anode mixture in a mass ratio of 10:90 into a three-dimensional mixer for uniform mixing to obtain a mixed material, and the mixing time is 30 minutes. Then, adding the silane coupling agent in a mass ratio of 0.5wt% into the bio-asphalt and epoxy resin mixed binder to obtain a strong wetting binder.

[0052] S6. The mixed material and the strong wetting binder are heated and kneaded in a mass ratio of 85:15, vibrated and formed, high-temperature calcined and shaped to obtain a prebaked anode for aluminum. The apparent density of the prebaked anode is 1.55 g / cm 3 , compressive strength is 33MPa, room temperature resistivity is 56μΩ·m, ash content is 0.4wt%, and CO2 reactivity is 84%.

[0053] Embodiment 3

[0054] A method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries, comprising the following steps:

[0055] S1. Multi-level refinement of the carbon slag from the wet leaching of retired ternary lithium batteries to obtain pre-treated materials with a particle size range of <0.074mm.

[0056] S2. The pretreated material and ammonium bifluoride are added to the polytetrafluoroethylene liner at a mass ratio of 1:0.8, and then polytetrafluoroethylene grinding balls are added at a ball-to-material mass ratio of 10:1 and sealed. The polytetrafluoroethylene liner is further loaded into a multi-external field coupling enhanced reaction device. The reaction temperature is 180°C, the reaction time is 60min, and the vibration frequency is 1000r / min.

[0057] S3, after the reaction is completed, the remaining solid material is subjected to a first-stage water washing treatment according to a liquid-solid ratio of 25:1, and after filtering, leaching residue 1 and leachate 1 are obtained; then, the leaching residue 1 is subjected to a second-stage water washing treatment according to a liquid-solid ratio of 20:1, and after filtering, leaching residue 2 and leachate 2 are obtained; further, a silane coupling agent is added to the aqueous solution according to a volume ratio of 0.3%, and then the leaching residue 2 is subjected to a third-stage water washing treatment according to a liquid-solid ratio of 15:1, and after filtering, a modified material and leachate 3 are obtained. The carbon content of the modified regenerated graphite is 99.97wt%, and the contact angle is 15.65°.

[0058] S4, the leachate 1 is subjected to alkaline impurity removal treatment, and then the pH value is adjusted to 2.5 with hydrofluoric acid, and the digestion agent is recovered by freeze concentration and circulated for multi-field coupling enhanced reaction. The leachate 2 is circulated in countercurrent for the first stage water washing treatment, and the leachate 3 is supplemented with a modifier and reused for the third stage water washing treatment. The recovery rate of ammonium bifluoride is 89.65%.

[0059] S5, adding the modified material, the electric calcined anthracite and the artificial graphite mixture in a mass ratio of 30:70 into a three-dimensional mixer for uniform mixing to obtain a mixed material, and the mixing time is 120 minutes. Then, adding the silane coupling agent in a mass ratio of 0.8wt% into the modified asphalt and coal tar mixed binder to obtain a strong wetting binder.

[0060] S6. The mixed material and the strong wetting binder are heated and kneaded in a mass ratio of 84:16, vibrated and formed, high-temperature calcined and shaped to obtain a cathode carbon block for aluminum. The apparent density of the cathode carbon block is 1.61 g / cm 3 , compressive strength is 31MPa, room temperature resistivity is 22μΩ·m, ash content is 2.1wt%, and sodium expansion rate is 0.3%.

[0061] Embodiment 4

[0062] A method for regenerating and modifying graphite in carbon slag extracted by wet leaching of retired lithium batteries, comprising the following steps:

[0063] S1. Multi-level refinement of the carbon slag extracted from the wet leaching of retired ternary lithium batteries to obtain pre-treated materials with a particle size range of <0.15mm.

[0064] S2. Add the pretreated material and ammonium bifluoride into the polytetrafluoroethylene liner at a mass ratio of 1:1, then add polytetrafluoroethylene grinding balls at a ball-to-material mass ratio of 8:1 and seal, and further install the polytetrafluoroethylene liner into a multi-external field coupling enhanced reaction device, with a reaction temperature of 200°C, a reaction time of 50min, and a vibration frequency of 1400r / min.

[0065] S3, after the reaction is completed, the remaining solid material is subjected to a first-stage water washing treatment according to a liquid-solid ratio of 30:1, and after filtering, leaching residue 1 and leachate 1 are obtained; then, the leaching residue 1 is subjected to a second-stage water washing treatment according to a liquid-solid ratio of 25:1, and after filtering, leaching residue 2 and leachate 2 are obtained; further, a silane coupling agent is added to the aqueous solution according to a volume ratio of 0.5%, and then the leaching residue 2 is subjected to a third-stage water washing treatment according to a liquid-solid ratio of 20:1, and after filtering, a modified material and leachate 3 are obtained. The carbon content of the modified regenerated graphite is 99.95wt%, and the contact angle is 16.91°.

[0066] S4, the leachate 1 is subjected to alkaline impurity removal treatment, and then the pH value is adjusted to 2 with hydrofluoric acid, and the digestion agent is recovered by freeze concentration and circulated for multi-field coupling enhanced reaction. The leachate 2 is circulated in countercurrent for the first stage water washing treatment, and the leachate 3 is supplemented with a modifier and reused for the third stage water washing treatment. The recovery rate of ammonium bifluoride is 88.43%.

[0067] S5, adding the modified material and the mixture of electric calcined anthracite, artificial graphite and asphalt coke in a mass ratio of 50:50 into a three-dimensional mixer for uniform mixing to obtain a mixed material, and the mixing time is 60 minutes. Then, adding the silane coupling agent in a mass ratio of 1.0wt% to the modified asphalt, coal tar and phenolic resin mixed binder to obtain a strong wetting binder.

[0068] S6. The mixed material and the strong wetting binder are heated and kneaded in a mass ratio of 83:17, vibrated and formed, calcined at high temperature and shaped to obtain a cathode carbon block for aluminum. The apparent density of the cathode carbon block is 1.59 g / cm 3 , compressive strength is 25MPa, room temperature resistivity is 28μΩ·m, ash content is 1.4wt%, and sodium expansion rate is 0.5%.

[0069] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries, characterized in that: The steps include: S1. Perform multi-level refinement on the carbon slag extracted by wet leaching of retired lithium batteries to obtain pre-treated materials; S2, adding the pretreated material and the digester into the polytetrafluoroethylene liner, then adding the polytetrafluoroethylene grinding balls and sealing, and then placing the polytetrafluoroethylene liner into the multi-external field coupling enhanced reaction device for reaction; S3, after the reaction is completed, the remaining solid material is subjected to a first-stage water washing treatment, and after filtering, a leached residue 1 and a leached liquid 1 are obtained; then the leached residue 1 is subjected to a second-stage water washing treatment, and after filtering, a leached residue 2 and a leached liquid 2 are obtained; then, the leached residue 2 is subjected to a third-stage water washing treatment with an aqueous solution added with a modifier, and after filtering, a modified material and a leached liquid 3 are obtained; S4, subjecting leachate 1 to alkaline impurity removal treatment, and then adjusting the pH value with a buffer, recovering the digestion agent by freeze concentration, and recycling it for multi-external field coupling enhanced reaction; leachate 2 is countercurrently circulated for a first-stage water washing treatment, and leachate 3 is supplemented with a modifier and reused for a third-stage water washing treatment; S5, mixing the modified material with the carbon aggregate to obtain a mixed material, and then adding the modifier to the binder to obtain a strong wetting binder; S6. The mixed material and the strong wetting binder are subjected to heating, kneading, vibration molding, high-temperature roasting and shaping treatment to obtain a carbon material product for aluminum.

2. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In the step S1, the particle size range of the pretreated material is any one of <1mm, <0.5mm, <0.15mm, and <0.074mm; the lithium battery is one or more of a ternary lithium battery, a lithium cobalt oxide battery, a lithium iron phosphate battery, and a lithium manganese oxide battery.

3. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In the step S2, the digester is one or more of ammonium bifluoride, ammonium fluoride, sodium bifluoride, and sodium hydroxide; the mass ratio of the pretreated material to the digester is 1:(0.1-1).

4. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In the step S2, polytetrafluoroethylene grinding balls are added according to a ball-to-material mass ratio of (1-20):1; the reaction temperature is 100-200°C, the reaction time is 10-60min, and the vibration frequency is 200-2000r / min.

5. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In step S3, the liquid-solid ratio during the first water washing treatment is (5-40):1; the liquid-solid ratio during the second water washing treatment is (5-30):1; the liquid-solid ratio during the third water washing treatment is (5-20):1; the water washing temperature is 20-90°C, and the water washing time is 10-100 min.

6. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In step S3, the modifier is one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; and the amount of the modifier added is 0.1 to 10% of the volume of the aqueous solution.

7. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In step S4, the buffer solution is one or more of hydrofluoric acid, ammonium bifluoride, ammonium fluoride, and carbonic acid; and the pH value is adjusted to 1-4 using the buffer solution.

8. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In the step S5, the mass ratio of the modified material to the carbon aggregate is 1:99-50:50; the mixing time is 30-180 min; the carbon aggregate is one or more of electrically calcined anthracite, artificial graphite, asphalt coke, calcined petroleum coke, and residual anode.

9. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In step S5, the binder is one or more of modified asphalt, bio-asphalt, coal tar, epoxy resin, and phenolic resin; and the amount of the modifier added is 0.01 to 1 wt % of the binder.

10. The method for regenerating and modifying graphite from carbon slag extracted by wet leaching of retired lithium batteries according to claim 1, characterized in that: In the step S6, the mass ratio of the mixed material to the strong wetting binder is 80:20-90:10; the carbon material product for aluminum is a prebaked anode or cathode carbon block.

Citation Information

Patent Citations

  • A method for resource-based treatment of decommissioned battery carbon residue

    CN112086703B

  • A method for resource-based treatment of decommissioned battery carbon residue

    CN115304059B

  • Method for preparing porous graphite by using waste lithium ion battery carbon residue

    CN116639686A

  • Method for recovering graphite from waste carbon residues of retired lithium ion batteries

    CN116969453A